Physical and physical characterization of prebiotic caprine yogurt added in mandacaru and passion fruit jelly (Research, Society and Development, 2020)
The aim of the research was to prepare prebiotic goat yogurt with jelly from the pulp of mandacaru and passion fruit and, subsequently, perform physical and physical-chemical analyzes. Two treatments of goat yogurt were processed with 15% of  mandacaru (Cereus jamacaru) and passion fruit (Passiflora edulis Sims.) jelly, to mention: CY (Controll Caprine Yogurt ), added from the starter culture Streptococcus Salivarius Subsp. Termophillus and YPREB (Prebiotic Caprine Yogurt), added by the Prebiotic Fiber Oligofructose (PFO) additioned to the starter culture. The samples were submitted to physical and physical-chemical analyzes, the processing of the yoghurts was carried out in triplicate, which were analyzed at times 1, 7, 14, 21 and 28 days of cold storage (4 ± 1 ° C). In view of the data analyzed, the yogurts showed physical and physical-chemical properties appropriate to the product. For some parameters, there was an influence of the culture used; fiber and jelly, with emphasis on the parameters of Acidity, pH and Lactose. The results of this study showed a successful incorporation (culture, PFO and jelly), as ingredients to be inserted in a new dairy product.